PERTANGGUNGJAWABAN PIDANA TERHADAP PENGGUNAAN CITRA TANPA PERSETUJUAN DALAM KONTEN PORNOGRAFI BERBASIS ARTIFICIAL INTELLIGENCE - Nila Arzaqi; Deny Puspitasari (Yayasan Merassa Indonesia Publikasi, 2026)
The advancement of generative Artificial Intelligence technology has introduced a new threat in the form of synthetic pornographic content created using individuals' images without consent, commonly known as deepfake pornography. This phenomenon raises serious concerns in criminal law, particularly regarding gaps in existing regulations and the complexity of determining criminal liability. This study aims to analyze Indonesian positive law provisions, construct criminal liability frameworks, and identify law enforcement challenges regarding the non-consensual use of images in AI-based pornographic content. A normative juridical method with a descriptive-analytical approach was employed, utilizing statutory, conceptual, and case approaches. The findings indicate that the Pornography Law, Electronic Information and Transactions Law, Personal Data Protection Law, and the New Criminal Code can be applied teleologically, yet contain normative gaps as none explicitly regulates AI-generated synthetic content. Criminal liability may be imposed upon active users as primary perpetrators, content distributors, platform developers, and content commissioners under the deelneming construction. Law enforcement faces juridical, technical-forensic, and institutional obstacles requiring a comprehensive approach through regulatory reform, digital forensic capacity building, victim protection, and digital platform accountability.